2016
DOI: 10.1165/rcmb.2015-0152oc
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Signaling through the Lysophosphatidic Acid-1 Receptor Is Required for Alveolarization

Abstract: Lysophosphatidic acid (LPA) signaling through one of its receptors, LPA 1 , contributes to both the development and the pathological remodeling after injury of many organs. Because we found previously that LPA-LPA 1 signaling contributes to pulmonary fibrosis, here we investigated whether this pathway is also involved in lung development. Quantitative assessment of lung architecture of LPA 1 -deficient knockout (KO) and wild-type (WT) mice at 3, 12, and 24 weeks of age using design-based stereology suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…We found that LPAR1-deficiency leads to alveolar enlargement or emphysema and decreased pulmonary vessel density in adult rats. This finding confirms observations in LPAR1 knockout mice showing that aberrant alveolar development caused by reduced secondary septation during early lung development was visible from 3 weeks after birth until adulthood (Funke et al, 2016 ). This explains why we did not observe alveolar enlargement in our previous study, in which the effects of LPAR1-deficiency on aberrant lung development were limited to the early neonatal period (Chen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that LPAR1-deficiency leads to alveolar enlargement or emphysema and decreased pulmonary vessel density in adult rats. This finding confirms observations in LPAR1 knockout mice showing that aberrant alveolar development caused by reduced secondary septation during early lung development was visible from 3 weeks after birth until adulthood (Funke et al, 2016 ). This explains why we did not observe alveolar enlargement in our previous study, in which the effects of LPAR1-deficiency on aberrant lung development were limited to the early neonatal period (Chen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…This explains why we did not observe alveolar enlargement in our previous study, in which the effects of LPAR1-deficiency on aberrant lung development were limited to the early neonatal period (Chen et al, 2016 ). LPAR1-deficiency may contribute to arrested alveolar development and reduced secondary septation by remodeling of elastic fibers, resulting in a reduction of disorganized septal fibers (Funke et al, 2016 ). The adverse effect of LPAR1 deficiency on alveolar development may limit the clinical usage of LPAR1 inhibitors for BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Enpp2 has been suggested, using genome-wide linkage analysis coupled with expression profiling, as a candidate gene controlling lung function, development and remodeling ( 123 ). Accordingly, Enpp2 −/− mice were found to be embryonically lethal ( 46 48 , 78 ), while Lpar1 −/− mice were shown to have reduced alveolar septal formation during development ( 124 ). In adult life, ATX is constitutively expressed by bronchial epithelial cells, in both humans, and mice, and can be detected in BALFs ( 49 , 125 ).…”
Section: Atx/lpa In Pulmonary Fibrosismentioning
confidence: 99%
“… 44 Approximately 50% of LPAR1 null mice demonstrate perinatal lethality due to craniofacial defects and difficulties suckling, 45 whilst in contrast, heterozygous LPAR1 ± deficient mice survive postnatally but demonstrate phenotypic lung abnormalities with impaired pulmonary alveolarisation. 46 LPAR2 null mice have normal viability however and show no phenotypic abnormalities. 47 LPA 3 is essential for normal embryo implantation, as such, LPAR3 null mice demonstrate abnormalities in reproduction.…”
Section: Role Of Atx-lpa Axis In Embryological Development and Normalmentioning
confidence: 98%
“… Funke et al 45 LPAR 1 ± heterozygous deficient mice Reduced alveolar septal formation. Contos et al 46 LPAR 2 -/- No phenotypic defect. Normal viability.…”
Section: Role Of Atx-lpa Axis In Embryological Development and Normalmentioning
confidence: 99%